(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Electrospinning is an advanced and versatile additive manufacturing method for the fabrication of small-diameter, nanofibrous scaffolds. However, because of various instabilities, electrospinning leads to unpredictable fiber deposition. Aligned and oriented nanofibers are required to mimic the mechanical anisotropy of soft tissue. With an adapted electrospinning setup the jet was focused or deflected between two auxiliary electrodes and thereby aligned. Tubular grafts with different fiber orientations were manufactured and evaluated in ultimate tensile tests. Fiber orientation affected the maximum tensile force and the compliance in the physiologic blood pressure range.